Carrying Capacity Atribute as Instrument of Sustainable Marginal Shrimp Pond Management at Lowita Minapolitan Estate, District of Pinrang - Hattah Fattah, Muhammad; Sitti Rahbiah, Asbar; Firmansyah Putra, dan (International Journal of Engineering and Technology, 2019)
The period of pond shrimp and fish cultivation recovery potentially triggers cultivation area extention exceeding environmental carrying capacity and leads to massive harvest failure. The research was conducted in Lowita Minopolitan Estate, district of Pinrang, South Sulawesi province. The analysis of environmental carrying capacity was conducted through capacity of dissolved oxygen availability. These approaches result in different pond extentions based on technology levels; intensive, semi-intensive, and traditional. The daily volume of sea water available on the beach for the cultivation is 3,154,765 m3 dy-1 in Lotang Solo village, 6,688,442 m3 dy-1 in Wiringtasi, and 3,590,424 m3 dy-1 in Tasiwalie. The waters environment carrying capacity is categorized as low at intensive cultivation pond. In case all pond areas are developed for traditional cultivation in Tasiwalie, Wiringtasi, and Lotang Salo with optimum production of 250 kg ha-1 CS-1, the allowed pond area that does not exceed the carrying capacity will successively be 1,966.18 ha, 557.37 ha, and 157.73 ha.Â